Mechanizm upolitycznienia przygotowań do obchodów 60. rocznicy wydarzeń na Wołyniu – wydarzenia z 1943 roku w dyskursie politycznym 2003 roku - Jędraszczyk, Katarzyna; Jędraszczyk, K. (Волинський національний університет імені Лесі Українки, 2012)
Механізм політизації підготовки до 60-ї річниці на Волині 1943 р. в політичному дискурсі 2003 р. У статті подано аналіз політичних тенденцій у 2003 р., пов’язаних із проблемою спільного польсько-українського відзначення 60-ї річниці трагічних подій на Волині 1943 р. In the article analyzes political trends in 2003 in connection with the joint Polish-Ukrainian celebration of the anniversary of the tragedy in Volyn in 1943.
Politicization of the Preparations for the 60th Аnniversary of the Tragedy in Volyn Events of 1943 in Political Discourse in 2003
Keywords: українсько-польські відносини; річниця подій на Волині; історія і політика; Polish-Ukrainian relations; anniversary of the tragedy in Volyn; history and politics